Perception of Medication-related Osteonecrosis of the Jaws among Iraqi Medical Specialists - Al-Samman, Abdurrahman A.; Al-Ani, Rand Sh. (European Dental Research and Biomaterials Journal, 2020)
Objective Osteonecrosis of the jaws is the adverse effect of antiresorptive and antiangiogenic agents, which is termed as medication-related osteonecrosis of the jaws (MRONJ). This complication, which is prominent and growing, is seen in the oral and maxillofacial region. This cross-sectional survey aimed to evaluate MRONJ awareness among Iraqi medical specialists.Materials and Methods A questionnaire-based survey was performed on medical specialists practicing general surgery, urology, orthopedics, rheumatology, and oncology. The questionnaire consisted of four questions regarding drug prescription, patients’ preparation before drug administration, in addition to awareness and knowledge about MRONJ.Results Among 132 specialists, 57% did not prescribe such drugs. A significant difference existed among groups regarding dental referral, and MRONJ awareness and knowledge. The highest rates were seen in the oncologist group.Conclusions Improvement of MRONJ perception and knowledge among medical specialists, besides implementation of dental referral, are essential in the prevention, diagnosis and treatment of MRONJ.
Keywords: perception; awareness; medication-related osteonecrosis of the jaws (MRONJ); questionnaire; specialists